Analysis of teleconnection between the Arctic Oscillation and South American cryosphere reduction - Bolaño Ortiz, Tomás Rafael (2019)
Fil: Bolaño Ortiz, Tomás Rafael. Universidad Tecnológica Nacional. Facultad Regional Mendoza. Grupo de Estudios Atmosféricos y Ambientales; Argentina